Demographic and Pathological Features of 430 Cases of Lymphoma from a Tertiary Hospital in Seremban, Malaysia (2015–2022) - Lim, Kean Ghee; Nasarudin, Muhammad Nabil; Khaw, Hui Yang Catherine; Lim, Jing Yee; Nordin, Nuha Sabrina; Hameed, Aishath Ana Ibrahim; Shamsudin, Noor Hasni; Burud, Ismail Abdul Sattar; Sood, Suneet (Malaysian Journal of Medical Sciences, 2025)
Background: Lymphoma, including both Hodgkin and non-Hodgkin types, is the fourth most common cancer in Malaysia. Few large studies have examined the frequencies and patterns of occurrence. This study describes the epidemiology of lymphoma in Malaysia based on cases from a public hospital, and compares demographic characteristics, distribution, subtypes, and anatomical sites.Methods: This retrospective study was conducted at Hospital Tuanku Ja’afar, Seremban, Malaysia. Admitted patients who had received medical or surgical treatment for lymphoma between 2015 and 2022 were reviewed.Results: A total of 430 cases were recorded. The distribution between extranodal (52.1%) and nodal (46.0%) lymphoma was nearly equal. Hodgkin lymphoma (HL) accounted for 16.3% of cases, with a mean age at presentation of 37 years, compared with 55.7 years for non-Hodgkin lymphoma (NHL). Diffuse large B-cell lymphoma (DLBCL) was the most common NHL subtype, representing 44.2% of all lymphoma cases. Among patients with staging information, 63% were diagnosed at stage IV. Males comprised 61% of the population. The predominant ethnic group was Malay (70.2%). The largest age group was 60 to 69 years (32.2%). Follicular lymphoma occurred less frequently than in Western and other Asian countries but was more common among ethnic Indians in Malaysia. Primary mediastinal large B-cell lymphoma, like other large B-cell lymphomas, was more frequent among Malays. Ethnic Indians also showed higher rates of HL (30.7%) and lower rates of DLBCL (25.6%).Conclusion: This study highlights many similarities in the distribution of lymphoma in Malaysia compared with patterns observed in the region and globally.